Pembinaan Akuntansi Berbasis SAK ETAP Untuk Perusahaan Manufaktur Mengunakan MYOB Accounting V17 Di SMK Batam Business School - Tukino Tukino; Baru Harahap; Algifanri Maulana (PUAN INDONESIA, 2021)
Vocational High Schools that are located close to each other, but have not synergized in the utilization of existing resources in each school are seen as less efficient. On the other hand, several vocational schools have adequate resources and potential to expand and simultaneously improve education services to the community through various education and training programs. In connection with these conditions, the Directorate of Vocational High Schools has programmed to combine these schools in one management and increase the capacity of Vocational High Schools through various education and training programs under the name Development of Large Vocational Schools. Financial statements function as a tool to analyze financial performance that can provide information about financial position, business, performance and cash flow so that it can be used as a basis for making economic decisions. The object of this service is aimed at the Batam Business School Vocational High School (SMK) around the Sekaran Village, where the majority of Batam Business School Vocational High School (SMK) players do not have financial reports. The purpose of this service program is to provide training to Batam Business School Vocational High School (SMK) actors in the preparation of accounting standards based on Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) as well as to design simple manual and computerized accounting systems that can help and facilitate students. Vocational High School (SMK) Batam Business School actors in making financial reports based on SAK ETAP